Body size and the relative abundance of species - Ulrich, Werner (Ecological Questions, 2008)
Existing models of species abundance distributions (SADs) can be divided into those that are based on concepts of common limited niche space (niche apportionment models, neutral models) and those that invoke standard statistical distributions (e. g. log-series, lognormal). While the first type of models assumes that competitive interactions lead to observed SADs, the models of the second type appear to be mainly statistical descriptors of SADs without deeper biological meaning. None of the models explicitly includes species body size as a factor influencing species abundances. Further, with the exception of recent neutral models they are not embedded into basic ecological and evolutionary models to explain local diversity and ecosystem functioning. Here I present a new random walk model of species abundances that is based on two well known ecological distributions, the abundance - body weight distribution and the species - body weight distribution to define long-term upper abundance boundaries (carrying capacities). I show that a simple random walk of species abundances around the carrying capacities not only generates observed SADs but is also able to explain other patterns of community structure like core - satellite distributions, temporal patterns of species turnover, variance - mean ratios, and biomass distributions.